LRR-Containing Oncofetal Trophoblast Glycoprotein 5T4 Shapes Neural Circuits in Olfactory and Visual Systems - Tsuboi, Akio (Frontiers in Molecular Neuroscience, 2020)
In mammals, sensory experience can regulate the development of various brain structures, including the cortex, hippocampus, retina, and olfactory bulb. Odor experience-evoked neural activity drives the development of dendrites on excitatory projection neurons in the olfactory bulb, such as mitral and tufted cells, as well as inhibitory interneurons. Olfactory bulb interneurons are generated continuously in the subventricular zone and differentiate into granule cells and periglomerular cells. However, it remains unknown what role each type of olfactory bulb interneuron plays in controlling olfactory behaviors. Recent studies showed that among the various types of olfactory bulb interneurons, a subtype of granule cells expressing oncofetal trophoblast glycoprotein 5T4 is required for simple odor detection and discrimination behaviors. Mouse 5T4 (also known as Tpbg) is a type I membrane glycoprotein whose extracellular domain contains seven leucine-rich repeats (LRRs) sandwiched between characteristic LRR-N and LRR-C regions. Recently, it was found that developmental expression of 5T4 increases dramatically in the retina just prior to eye opening. Single-cell transcriptomics further suggest that 5T4 is involved in the development and maintenance of functional synapses in a subset of retinal interneurons, including rod bipolar cells and amacrine cells. Collectively, 5T4, expressed in interneurons of the olfactory bulb and retina, plays a key role in sensory processing in the olfactory and visual systems.